PELAKSANAAN TUGAS POKOK STEWARD KITCHEN PAD FOOD AND BEVERAGE PRODUCT DEPARTMENT DI TURI BEACH RESORT BATAM - Nabila, Wahyu; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to determine the implementation of Steward SOP in the Food and Beverage Department at Turi Beach Resort Batam. This research uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurred by collecting data and information in the field. The key informants in this research are the Head Chef, SPV and employees. In this research, the data collection techniques used were interviews, observation and documentation. Based on the research results, it can be concluded. aspects of implementing the Standard Operation Procedure Steward are in line with the standard operational procedures listed in the hotel itself. However, there are a few obstacles in implementation due to the age of the employees at Steward. Most of the employees who work are still young and always bring feelings into the work environment. The efforts made by the hotel in implementing the Steward's Standard Operation Procedure in the Food and Baverage Product Department of Turi Beach Resort Batam is to monitor the Steward's work so that the implementation of the Standard Operation Procedure runs well. and smooth. Keywords: SOP, Steward, Turi beach